The zero-emissions cost of energy: a policy concept. (6th April 2021) - Beal, Colin M; King, Carey W
Abstract: The energy sector generates over 70% of global greenhouse gas (GHG) emissions, but existing energy-climate policies do little to reduce GHG emissions to prevent climate change. We present a new carbon tax policy concept in which energy users would be taxed an amount equal to the cost of cleaning up the emissions that they create, wherein the tax revenues would be used to operate negative emissions technologies. The policy is based on applying the zero-emissions cost (ZEC) metric to energy prices, which includes the 'regular' cost of an energy source plus the cost of sequestering its emissions. Using the ZEC, (a) the energy sector would be emissions-neutral, (b) biofuels would be cheaper than petroleum fuels, and (c) renewable electricity would be cheaper than fossil-fuel electricity. We calculate the energy spending as a fraction of gross domestic product for 'regular' and ZEC cost scenarios. Implementing the ZEC carbon-tax policy would enable a monumental shift to a net-zero emissions energy sector, but carries a significant risk of causing an economic recession. The summary point of this commentary is to demonstrate a pathway to achieve net-zero GHG emissions from the US energy sector, and to contemplate the associated economic impacts on our society.